Pleuroscopy in exudative pleural effusion: A North Malaysia experience - Alaga, Arvindran; Hamzah, Kamarul Ariffin; Tan, Eng Liang; Ibrahim, Muhamad Amin; Md Kassim, Razul Md Nazri (The Interventionalist Journal, 2021)
Background: Pleuroscopy is one of the investigation modalities available for further evaluation of exudative pleural effusion. Aims of this study is to determine the diagnostic yield and common cause for pleural effusion that underwent pleuroscopy in Respiratory department, Hospital Sultanah Bahiyah . Methods: This is a retrospective descriptive analysis study of 106 patient who underwent pleuroscopy in Hospital Sultanah Bahiyah between July 2014 till Dec 2016. Hospital Sultanah Bahiyah is the only centre doing this procedure in North Malaysia. Result: Biopsy were done in 91% of the cases with diagnostic yield of up to 97%. Most common finding were malignancy (55%) with adenocarcinoma being the commonest subtype. Second commonest finding are granulomatous inflammation (19%) which is not surprising given our burden of tuberculosis. Majority of our patient were male (58%) with mean age of 60 years old. With regard to safety only one case develop complication where the patient develops re-expansion pulmonary oedema with no procedure related mortality. Conclusion: Pleuroscopy is a very safe procedure. Despite the high Tuberculosis burden in Malaysia the most common cause for exudative pleural effusion were due to malignancy, hence pleuroscopy should be consider in all cases of exudative pleural effusion.